2022
DOI: 10.4103/0304-4920.358234
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C Supplementation Attenuates Oxidative Stress and Improves Erythrocyte Deformability in Cardiac Surgery with Cardiopulmonary Bypass

Abstract: Cardiopulmonary bypass (CPB) depletes endogenous Vitamin C and generates oxidative stress in cardiac surgery. This study aimed to clarify whether Vitamin C supplementation reduces oxidant production and improves erythrocyte deformability in cardiac surgery with CPB. In a randomized and controlled design, 30 eligible patients undergoing cardiac surgery with hypothermic CPB were equally assigned to the Vitamin C group and control group. Subjects of the Vitamin C group and control group received an intravenous in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…It also contributes to the immune system in processes such as neutrophil chemotaxis, phagocytosis by lymphocytes and cell renewal [136,137]. In addition, vitamin C can phosphorylate the signaling pathway in erythrocytes, in addition to stimulating endothelial nitric oxide production, which can reduce blood loss and vasoplegic syndrome [138,139].…”
Section: Vitamin Cmentioning
confidence: 99%
See 1 more Smart Citation
“…It also contributes to the immune system in processes such as neutrophil chemotaxis, phagocytosis by lymphocytes and cell renewal [136,137]. In addition, vitamin C can phosphorylate the signaling pathway in erythrocytes, in addition to stimulating endothelial nitric oxide production, which can reduce blood loss and vasoplegic syndrome [138,139].…”
Section: Vitamin Cmentioning
confidence: 99%
“…Furthermore, studies have been demonstrated the benefit of vitamin C supplementation, contributing to the reduction of arrhythmias (mainly atrial fibrillation) and duration of mechanical ventilation, ICU and hospital stay, despite not having demonstrated an improvement in mortality [138][139][140][141][142]. Although its use is promising, even with limitations, studies that assess the form of administration, whether in bolus or continuous infusion, before, during or after CPB are necessary to better assess the effectiveness of vitamin C supplementation.…”
Section: Vitamin Cmentioning
confidence: 99%